2019
DOI: 10.1101/820969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analytic activation maps can help identify affective processes captured by contrast-based task fMRI: the case of threat-related facial expressions

Abstract: Meta-analysis of functional magnetic resonance imaging (fMRI) data is an effective method for capturing the distributed patterns of brain activity supporting discrete cognitive and affective processes. One opportunity presented by the resulting meta-analysis maps (MAMs) is as a reference for better understanding the nature of individual contrast maps (ICMs) derived from specific task fMRI data. Here, we compared MAMs from 148 neuroimaging studies representing the broad emotion categories of fear, anger, disgus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…To complement these univariate regions of interest (ROIs), we leveraged whole-brain patterns associated with reactivity, regulation, and valuation, and calculated individual expression of these patterns. Distributed patterns of neural activity associated with target psychological processes may be more sensitive than univariate indicators (Chang et al, 2015), and this approach has been shown to reliably index people's conscious decisions to regulate negative emotions (Doré et al, 2017), as well as capture negative affective states during a threat processing task (Kim et al, 2019). Another study showed that whole-brain patterns of activation that more closely resembled a meta-analytic map of cognitive reappraisal (Buhle et al, 2014) during exposure to emotionally evocative stimuli were linked with lower stress during the task, even when participants were not instructed to regulate (Shahane et al, 2019).…”
mentioning
confidence: 99%
“…To complement these univariate regions of interest (ROIs), we leveraged whole-brain patterns associated with reactivity, regulation, and valuation, and calculated individual expression of these patterns. Distributed patterns of neural activity associated with target psychological processes may be more sensitive than univariate indicators (Chang et al, 2015), and this approach has been shown to reliably index people's conscious decisions to regulate negative emotions (Doré et al, 2017), as well as capture negative affective states during a threat processing task (Kim et al, 2019). Another study showed that whole-brain patterns of activation that more closely resembled a meta-analytic map of cognitive reappraisal (Buhle et al, 2014) during exposure to emotionally evocative stimuli were linked with lower stress during the task, even when participants were not instructed to regulate (Shahane et al, 2019).…”
mentioning
confidence: 99%
“…To complement these univariate regions of interest (ROIs), we leveraged whole-brain patterns associated with reactivity, regulation, and valuation and calculated the individual expression of these patterns. Distributed patterns of neural activity associated with target psychological processes may be more sensitive than univariate indicators ( Chang et al , 2015 ), and this approach has been shown to reliably index people’s conscious decisions to regulate negative emotions ( Doré et al , 2017 ) as well as capture negative affective states during a threat-processing task ( Kim et al , 2019 ). Another study showed that whole-brain patterns of activation that more closely resembled a meta-analytic map of cognitive reappraisal ( Buhle et al , 2014 ) during exposure to emotionally evocative stimuli were linked with lower stress during the task, even when participants were not instructed to regulate ( Shahane et al , 2019 ).…”
mentioning
confidence: 99%